MUGHAL CARPET PAINTING (WITH REFERENCE TO LINE, COLOR AND ORNAMENTATION): मुगल कालीन चित्रकला (रेखा, रंग और अलंकरण के सन्दर्भ में) - Kumar Yadav, Santosh (International Journal of Research -GRANTHAALAYAH, 2014)
It is revealed from the above verses that the beautiful picture is formed by the collective union of the four, Rekha Rang Vrattana and ornamentation. These four elements play their important role in generating life in any picture. Without these elements, we cannot call any art complete. No matter how much changes have been made in art since the beginning of human civilization, these elements in art still have the same importance today as before. The only difference is that now the pattern of its use has changed. We have already described the importance of their use through one verse. And as far as their use in Mughal art is concerned, they have been used extensively in this art. It is appropriate to describe here that the style of art that flourished in Iran from the beginning of the religion of Islam was the foundation stone of ancient Indian art. It contained his deep impression. The depiction of human beings and living beings in the religion of Islam was completely against the religion. As a result, colors, lines, embellishments, fine ornamental figures and geometric shapes have evolved. With the advent of flexibility in religious fanaticism, the marking of animals - birds, human figures and flower leaves started which has been going on till today. The paintings of the early stages of Mughal art are influenced by the art of Iran. In which not only the subject but also the technique, medium, drawing and color planning are all based on Iranian style. As his art came close to Indian art, so the qualities of Indian art are seen in him. There are many qualities of Indian art in the art of the Mughal period, but we are going to describe three major qualities of them here: color, line and embellishments. उपरोक्त श्लोक से यह पता चलता है कि रेख रंग वत्र्तना और अलंकरण इन चारों के सामूहिक मिलन से ही सुन्दर चित्र का निर्माण होता है। ये चारो तत्च किसी भी चित्र मे प्राण उत्पन्न करने मे अपनी महत्वपूर्ण भूमिका निभाते है। इन तत्वों के बिना हम किसी भी कला को पूर्ण नही कह सकते है। मानवीय सभ्यता के शुरूआत से लेकर अब तक कला मे चाहे कितना भी परिवर्तन हुआ हो कला मे ये तत्व आज भी आज भी उतना ही महत्व रखते है जितना कि पहले। अन्तर बस इतना हुआ है कि अब इसके प्रयोग करने का स्वरूप बदल गया है। इनके प्रयोग की महत्ता का वर्णन हम पहले ही एक श्लोक द्वारा कर चुके है। और जहां तक मुगल कला मे इनके प्रयोग की बात है तो इस कला मे इनका प्रयोग बहुतायत हुआ है। हम यहां इस बात का वर्णन करना उचित होगा कि इस्लाम धर्म के शुरूआत से ही ईरान मे जो कला शैली पनपी वह प्राचीन भारतीय कला की आधार शिला थी। इसमे उसकी गहरी छाप निहित थी। इस्लाम धर्म मे मानव व जीवधारियों का चित्रण पूरी तरह से धर्म के विरूद्ध था। जिसके फलस्वरूप रंग, रेखा, अलंकरण, सूक्ष्म अलंकारिक आलेखनों एवं ज्यामितीय आकारों का विकसित रूप निखर कर आया है। धार्मिक कट्टरता मे लचीलापन आते ही पशु - पक्षियों, मानव आकृतियों और फूल पत्तियों का अंकन प्रारम्भ हो गया जो आज तक चला आ रहा है। मुगल कला के प्रारम्भिक अवस्था के चित्र ईरान की कला से प्रभावित है। जिनमें न केवल विषय ही बल्कि तकनीक, माध्यम, चित्रांकन और रंगयोजना आदि सभी ईरानी शैली पर आधारित है। जैसे जैसे उनकी कला भारतीय कला के समीप आती गई वैसे वैसे उसमे भारतीय कला के गुण नजर आने लगते है। मुगल काल की कला मे भारतीय कला के बहुत से गुण दिखते है परन्तु हम उनमे से तीन प्रमुख गुण रंग ,रेखा और अलंकरणका वर्णन यहा करनेजा रहे है